'The real power must be in the base' – Decentralised collective intellectual leadership in the European Action Coalition for the Right to Housing and to the City. (December 2021) - Bonfert, Bernd
The ongoing commodification of housing and urban space in Europe has led to the formation of a burgeoning housing movement, consisting of large anti-eviction networks in Southern Europe, as well as tenants' unions and right-to-the-city networks in Central and Northern Europe. These different forms of housing activism have become increasingly connected at the transnational level, primarily due to the work of the 'European Action Coalition for the Right to Housing and to the City'. Consisting of activist groups from over 20 different countries, this coalition facilitates mutual exchange, organises collective campaigns and has begun engaging in institutional advocacy at the European Union level. It steadily expands in size and tactical repertoire, aiming to develop a more unified transnational strategy for attaining affordable and self-determined living space across Europe. Drawing on the writings of Antonio Gramsci, this article makes the case that the 'European Action Coalition for the Right to Housing and to the City' increasingly performs the function of a 'collective intellectual' that organises a transnational struggle against neoliberal hegemony. Based on qualitative analyses of documents, interviews and field notes, it demonstrates that the 'European Action Coalition for the Right to Housing and to the City' exhibits a counter-hegemonic perspective that opposes neoliberal capitalism as a whole and manages to facilitate mutual solidarity across different activist communities explicitly on the basis of class struggle. At the same time, instead of organising a democratic centralist political project the 'European Action Coalition for the Right to Housing and to the City' pursues a more decentralised approach to collective intellectual leadership that prioritises domestic struggles, yet also lacks a cohesive long-term strategy.